Nanobioimaging: Intrinsically Fluorescent, Stealth Polypyrazoline Nanoparticles with Large Stokes Shift for In Vivo Imaging (Small 36/2018). Issue 36 (6th September 2018) - Mane, Shivshankar R.; Hsiao, I‐Lun; Takamiya, Masanari; Le, Dao; Straehle, Uwe; Barner‐Kowollik, Christopher; Weiss, Carsten; Delaittre, Guillaume
Abstract : In article number1801571, Christopher Barner‐Kowollik, Carsten Weiss, Guillaume Delaittre, and co‐workers report the straightforward synthesis of biocompatible stealth fluorescent nanoparticles. A mild photopolycondensation provides a polypyrazoline macromolecular chain, exhibiting a large Stokes shift, attached to a polyethylene glycol segment. The nanoparticles made thereof circulate for extended periods of time in the blood stream of model zebrafish embryos and are therefore promising for advanced bioimaging.